Lower cardiac vagal tone in non-obese healthy men with unfavorable anthropometric characteristics (Clinics, 2010)
OBJECTIVES: to determine if there are differences in cardiac vagal tone values in non-obese healthy, adult men with and without unfavorable anthropometric characteristics. INTRODUCTION: It is well established that obesity reduces cardiac vagal tone. However, it remains unknown if decreases in cardiac vagal tone can be observed early in non-obese healthy, adult men presenting unfavorable anthropometric characteristics. METHODS: Among 1688 individuals assessed between 2004 and 2008, we selected 118 non-obese (BMI